Seroprevalence and risk factors of caprine brucellosis in Khartoum state, Sudan - Mohamed, Eman Mohamed-Ahmed (Vet World, 2018)
AIM: This cross-sectional study was conducted from April to July 2012 in Khartoum state, Sudan, to determine the seroprevalence of brucellosis in goats and to investigate potential risk factors associated with this disease. MATERIALS AND METHODS: A total of 307 serum samples were collected from both sexes of goats in four different localities and were subjected to testing for brucellosis using rose bengal plate test (RBPT), serum agglutination test (SAT), and competitive enzyme-linked immunosorbent assay (cELISA). RESULTS: The overall seroprevalence was 11.4% (n=35) with a 95% confidence interval (CI) ranging from 7.80 to 15.0. Out of these 35 RBPT-positive samples, the positivity of 18 and 17 were confirmed by SAT and cELISA, respectively. A significant statistical variation was observed between brucellosis seroprevalences in goats purchased from local animal markets and goats that were raised at the farm. Conversely, such significant variations were not observed among the categories of other risk factors with seroprevalences ranging from 3.0% (95% CI between 0.40 and 7.20) to 16.3% (95% CI between 10.4 and 22.3). Location (χ(2)=9.33, df=3, p=0.02), breed (χ(2)=3.52, df=1, p=0.05), herd size (χ(2)=6.59, df=2, p=0.03), and herd expansion (χ(2)=5.39, df=1, p=0.02) were associated with RBPT-positive status for brucella in the two-tailed Chi-square test. In addition, Sharq an-Nil locality and goats raised at the farm had increased odds of being RBPT positive. CONCLUSION: Brucellosis was detected in goats in all surveyed localities. An effort should be made to educate goat owners/herders about brucellosis as well as about the importance of vaccination.